Hypertension Risk Factors in Batu Ampar Public Health Center West Borneo - Putu Devara Karunia Esa (Science Midwifery, 2022)
Many people do not know that they have been diagnosed with hypertension until complications arise. Hypertension is a non-communicable disease caused by many factors. The risk factors that influence the incidence of hypertension are divided into two: modifiable and non-modifiable risk factors. Thus far, there is no data on risk factors for hypertension in the Batu Ampar Public Health Center work area. The objective of research is knowing the risk factors for hypertension in the working area of Batu Ampar Public Health Center. An observational study with a cross sectional design conducted at the Batu Ampar Public Health Center from April to June 2022. The variable data collected were age, gender, education level, occupation, obesity, smoking habits, exercise habits, alcohol consumption, salt consumption and fruit consumption. and vegetables. Of the 150 respondents (75 with hypertension and 75 without hypertension) it was found that age, occupation, alcohol consumption and salt consumption were risk factors. The probability of hypertension having these four risk factors is 97%. Risk factors for hypertension in the working area of Batu Ampar Public Health Center are age, occupation, alcohol consumption and salt consumption.